IDENTIFIKASI DAN ANALISIS KONFLIK SOSIAL DI KOTA BAU-BAU - La Janu (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2016)
This study aims to identify and analyze social conflicts in Bau-Bau City, especially to get a picture of the identity of the stakeholder involved either directly or indirectly in the conflict, the types of relationships of the stakeholder involved in the conflict, the various interests involved in the conflict, various issues who are involved in the conflict and who can be encouraged in conflict resolution. The data collection in this research was based on information from several sources, that was through online media, literature study, and field research, by observing the conflict incident and meeting the informant directly, then conducting the interview related to conflict incident. The collected data then analyzed as descriptive qualitative. The results of this study indicated that there were 3 social conflicts that occurred in Baubau City in the last 4 years due to structural conflict, conflict of interest and psychological conflict. The impact of the conflict was 1 person died, 7 people injured, 1 unit of government facilities, fifteen homes and 4 motorcycle heavily damaged. These two conflicts were resolved by deliberation and the remainder was settled through legal channels or authorities. Keywords: identification, analyse, social conflict